2008
DOI: 10.1007/s15010-008-7378-7
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ and Granulocyte-Macrophage Colony Stimulating Factor Therapy in Three Patients with Pulmonary Aspergillosis

Abstract: An immune response mediated by type 2 cytokines is thought to contribute to the development and unfavorable outcome of aspergillosis. Adjuvant therapy with interferon-gamma (IFN-gamma) and granulocyte-macrophage colony stimulating factor (GM-CSF) was added to antifungal treatment in three nonneutropenic patients (one HIV-positive and two HIV-negative patients) with culture proven aspergillosis refractory to classical antifungal therapy. Clinical improvement was observed concomitantly with an increase in periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 17 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…In a similar animal model, it was shown that NK cell-derived IFN-g was the protective factor against IA (8,9). Clinical data confirmed an antifungal and, more specifically, the anti-Aspergillus activity of IFN-g (7,(10)(11)(12)(13)(14). These studies attributed the beneficial effect of IFN-g to its immunoregulatory role with phagocytes of the innate immune system, which are conventionally involved in the host defense against A. fumigatus (11,15).…”
Section: N Atural Killer Cells Are Cd56mentioning
confidence: 79%
“…In a similar animal model, it was shown that NK cell-derived IFN-g was the protective factor against IA (8,9). Clinical data confirmed an antifungal and, more specifically, the anti-Aspergillus activity of IFN-g (7,(10)(11)(12)(13)(14). These studies attributed the beneficial effect of IFN-g to its immunoregulatory role with phagocytes of the innate immune system, which are conventionally involved in the host defense against A. fumigatus (11,15).…”
Section: N Atural Killer Cells Are Cd56mentioning
confidence: 79%
“…Thus, novel stand-alone or adjunctive therapeutic options are sought after for the treatment of IA. One line of research that holds great promise for improving IA outcomes is modulation of the host immune response (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…72 A murine model of systemic zygomycosis showed greater reduction in fungal burden when GM-CSF was combined with liposomal amphotericin B and compared with liposomal amphotericin B alone, and published reports have shown the successful use of GM-CSF and interferon-g as adjunctive therapy for refractory invasive fungal infections in neutropenic and nonneutropenic patients. [73][74][75] In a randomized, double-blind, placebo-controlled trial of 38 patients with severe sepsis or septic shock and sepsis-induced immunosuppression (characterized by monocytes with reduced HLA class II cell surface expression), administration of GM-CSF was associated with increased cell surface expression of HLA markers and enhanced proinflammatory cytokine production, a shorter duration of mechanical ventilation, and improved Acute Physiology and Chronic Health Evaluation II (APACHE II) scores immediately after the course of GM-CSF. 76 Although interesting, larger studies that focus on clinically relevant outcomes are needed, particularly because previous studies have shown a GM-CSF-induced improvement in ex vivo immune function without a corresponding improvement in morbidity or mortality.…”
Section: Gm-csfmentioning
confidence: 99%